Birth Order Effects, Parenting Style, and Son Preference - Jun Hyung Kim; Shaoda Wang (Global Labor Organization (GLO), 2021)
While it is well known that there are systematic birth order effects on life cycle outcomes, there is less consensus about underlying channels and mechanisms of birth order effects. We find negative birth order effects among Chinese adolescents, favoring earlier-born children within household in academic achievement and cognitive skill measures. We highlight harsh parenting as a novel channel of birth order effects, in which earlier-born children are less likely to be physically punished by their parents. Focusing on son preference as a potential mechanism generating birth order effects, our tests show limited support for the existence of son preference among Chinese siblings. These findings are in contrast to positive birth order effects and strong evidence of son preference among earlier generations of Chinese siblings reported in the literature, suggesting weakened role of son preference within families in contemporary China.
Keywords: I20; J10; J13; 330; birth order effect; parenting style; academic achievement; cognitive skill; son preference